1996
DOI: 10.1063/1.116886
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the buffer layers on the morphology and the transport properties in InAs/(Al,Ga)Sb quantum wells grown by molecular beam epitaxy

Abstract: The growth of modulation-doped InAs/(Al,Ga)Sb quantum wells on GaAs substrates employing molecular beam epitaxy requires care in the nucleation and the use of buffer layers to achieve high quality material. Despite a 7% lattice mismatch between the substrate and the active layers, fully relaxed epitaxial growth can be accomplished, and quantum wells with electron sheet concentrations of 7×1012 cm−2 having low-temperature mobilities as high as 300 000 cm2/V s have been routinely fabricated recently in our labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Kroemer's group has also shown that the roughness is different using an AlSb or a GaSb buffer grown on a GaAs substrate [3]. The roughness generated during the AlSb nucleation layer is smoothed by the growth of a GaSb layer although it is preserved by an AlSb growth.…”
Section: Results Ofmentioning
confidence: 96%
See 2 more Smart Citations
“…Kroemer's group has also shown that the roughness is different using an AlSb or a GaSb buffer grown on a GaAs substrate [3]. The roughness generated during the AlSb nucleation layer is smoothed by the growth of a GaSb layer although it is preserved by an AlSb growth.…”
Section: Results Ofmentioning
confidence: 96%
“…The conventional technique of a Si plane in the barrier does not work because Si is amphoteric in III-V compounds and acts as a p-type dopant in antimonide-based materials [5]. An alternative solution consists in using Te as n-type dopant in the AlSb barrier [3]. Unfortunately, Te presents a high vapour pressure resulting in memory effects in the molecular beam epitaxy (MBE) chamber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first key issue is the growth of low dislocation density GaAs-based SLs, since any roughness may lead to inferior lateral transport in the InAs/GaSb SLs [8] and in-homogeneity of the band gap. In our experiment, we used an AlSb interfacial misfit mode (IMF) quantum dot (QD) and an AlSb/GaSb SLs as the buffer layers on GaAs substrates.…”
Section: Methodsmentioning
confidence: 99%
“…3 This results in a tensile strain in the InAs channel with respect to the AlSb metamorphic buffer leading to the formation of threading dislocations. 4 Anisotropic electron transport in HEMT devices based on strained layers of III-V alloys has been reported earlier. 5,6 However, no anisotropy behavior in InAs/ AlSb heterostructures has been reported so far.…”
mentioning
confidence: 99%